The effect of sanding on the wettability and surface quality of imbuia, red oak and pine wood veneers - Cordeiro, Lincoln Audrew; de Miranda, Bruno; Carneiro, Mayara Elita; Missio, André Luiz; Klock, Umberto; Gonzalez de Cademartori, Pedro Henrique (Maderas. Ciencia y Tecnología, 2023)
The finishing quality of wood products depends on the material's surface and its intrinsic properties. Dynamic wettability is a simple and efficient way to understand the behavior of materials related to solid-liquid interactions according to theoretical and practical perspectives. Thus, we sought to investigate the wettability of imbuia (Ocotea spp.), red oak (Quercus spp.), and pine (Pinus elliottii) woods and its effects before and after sanding. Through the sessile drop technique, we evaluated contact angle and work of adhesion. Sanding changed the samples’ surface quality due to the decrease in contact angle and the increase in the work of adhesion. In addition, the droplet spreading and adsorption observed on the surface of the woods are an indicator of wettability. Pine and red oak had their dynamic contact angle reduced by up to 43 %. However, imbuia was less susceptible to the effects of sanding, since it was found to be a more hydrophobic species; thus, this wood has a more stable surface in terms of dynamic wettability. This may be a result of the effect of low molecular weight compounds on the surface of imbuia wood. The preparation of the wood surface depends on a synergy between the finishing processes and the chemical composition of the surface. Therefore, the results found can indicate which coatings are more suited to these woods.